Gastroprotective activity of the rhizome ethanol extract of Zingiber simaoense Y. Y. Qian in rats - Pareeya Baiubon (2018)
© 2016 Elsevier Ireland Ltd Ethnopharmacological relevance Zingiber simaoense Y. Y. Qian belongs to the Zingiberaceae family. Its rhizome has been used in Thai folk medicine to relieve gastric disorders; however, scientific evidence of its pharmacological activities has not yet been revealed. Aim of the study This study was designed to validate the gastroprotective activity and to identify possible mechanisms of gastroprotection of Z. simaoense rhizome ethanol extract (ZSE) in rats. Materials and methods The gastroprotective effect of ZSE was tested using models of gastric ulcers induced by acidified ethanol, indomethacin, and restraint water immersion stress. Models for determination of gastric wall mucus secretion and plasma malondialdehyde levels as well as pylorus ligation were used to explore the mechanisms of action. Results After oral administration by intragastric gavage, ZSE 7.5, 15, and 30 mg/kg or cimetidine 100 mg/kg significantly inhibited the formation of gastric ulcer in all gastric ulcer models. The gastric wall mucus amount was significantly higher than that of the ulcer control group, plasma malondialdehyde levels were normalized, and gastric secretion was partly inhibited by pretreatment with ZSE. Conclusions This study demonstrates the gastroprotective activity of ZSE in rats. The mechanisms of action of ZSE may depend on its ability to maintain the integrity of gastric wall mucus through the protection of gastric mucus, and/or by increasing the gastric mucus synthesis and secretion through prostaglandin synthesis. Moreover, the antioxidant activity of ZSE may also contribute to its mechanism of gastroprotection.